COMPARATIVE ANALYSIS OF STATE ADMINISTRATIVE COURT AUTHORITY BETWEEN INDONESIA AND EGYPT - Alaqab, Bian; Salwa Agustin, Fahriyah; Tahir, Erdin (Prodi Magister Ilmu Hukum Fakultas Hukum Universitas Singaperbangsa Karawang, 2024)
Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. H Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. Administrative courts, specialized judicial bodies, resolve disputes related to administrative law and government actions. State Administrative Courts in various countries, exemplified by Egypt and Indonesia, represent critical pillars of administrative justice. However, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court. owever, their structures, functions, and roles differ significantly. This paper aims to comprehensively analyse and compare these courts, exploring their importance, theoretical underpinnings, and implications within legal systems .It seeks to elucidate the significance of researching State Administrative Courts, emphasizing the importance of comparative analysis between Egypt and Indonesia. It aims to examine theoretical concepts within the context of administrative courts. Egypt and Indonesia showcase distinct strengths and challenges within their administrative justice systems, providing insights for potential reforms and enhancements in administrative law mechanisms. Keywords: Administrative laws; Indonesia and Cairo; State administrative court.